Using paleoecological data to inform decision making: A deep-time perspective - Dowsett, Harry; Jacobs, Peter; de Mutsert, Kim (Frontiers in Ecology and Evolution, 2022)
Climate models project conditions for the end of this century that are outside of the human experience. These future conditions may affect the resilience and sustainability of ecosystems, alter biogeographic zones, and impact biodiversity. Deep-time records provide insight into the climate system over millions of years providing examples of conditions different from the present day, and similar to model projections for the future. Deep-time paleontologic archives provide insight into how species and habitats responded to past climate conditions. Thus, paleoclimatology provides essential context for scientific understanding of climate change needed to inform resource management policy decisions. The Pliocene Epoch (5.3–2.6Ma) is the most recent deep-time interval with relevance to future global warming. Analysis of marine sediments using a combination of paleoecology, biomarkers, and geochemistry indicates a global mean annual temperature for the Late Pliocene (3.6–2.6Ma) ~3°C warmer than the preindustrial. However, the inability of state-of-the-art models to capture some regional features of Pliocene warming implies future projections using these same models may not span the full range of plausible future conditions. The Late Pliocene is one example of a deep-time interval relevant to management of biodiversity and ecosystems in a changing world. Pliocene SST's are used to drive a marine ecosystem model for the North Atlantic Ocean. Given Late Pliocene boundary conditions are roughly analogous to present day, driving the marine ecosystem model with Late Pliocene paleoenvironmental conditions allows policymakers to consider a future ocean state and associated fisheries impacts independent of climate models, informed directly by paleoclimate information.